The level of knowledge, attitude and practice towards Covid-19 immunisation among medical students in public medical schools in Malaysia - Mohamad Zainal, Nurul Hayati; Mohammed Ayyub, Safiyya; Yi, Chang Fang; Zaman, Arif Najmi Shahrir; Mohd Nor, Nurul Huda; Omar, Norsuhana; Ku Mohd Noor, Ku Mastura; Hamimi Wahid, Hanan (Faculty of Medicine, University of Malaya, 2023)
COVID-19 is a highly contagious disease that caused a worldwide pandemic in 2020. Medical students are public advocates for COVID-19 vaccination to achieve herd immunity. Our objective is to ascertain the level of knowledge, attitude, and practice toward COVID-19 immunisation among medical students in Malaysia. The online study included four public universities in Peninsular Malaysia: Universiti Putra Malaysia, International Islamic University Malaysia, Universiti Sains Malaysia and Universiti Sains Islam Malaysia. Data collected include sociodemographic characteristics, history of COVID-19 infection, knowledge, attitude and practice towards COVID-19 immunisation. Analytical statistics were analysed with IBM Statistical Package Statistical Package for the Social Science (SPSS) v27.0 using Pearson chi-square or Fisher’s exact test (significant if p < 0.05). From the total of 427 respondents, 60.2 had good knowledge whereby clinical students 67.0 had a higher proportion of good knowledge as compared to preclinical students 53.5 (p = 0.004). Respondents in the age group of 21 to 24 years old (p < 0.001) and 25 to 29 years old (p = 0.016), and Indian ethnicity (p = 0.006) were more likely to have good knowledge. Respondents registered in Malaysia’s National COVID-19 vaccination program were considered as having a positive attitude (n = 264, 61.8). A vaccination rate of 100 was observed. In conclusion, 60.2 of medical students had good knowledge, 61.8 had a positive attitude and 100 were vaccinated in these four public medical schools in Malaysia. Sociodemographic factors (age group and Indian ethnicity) have an association with only good knowledge but none with the level of attitude and practice towards COVID-19 immunisation.